Extensions of schooling environments into the local community, and social construction of democracy in Spain (1931-1939). Contributions made by the Freinet pedagogical movement - José Luis Hernández Huerta (Cadernos de História da Educação)
This article highlights the social nature of the Freinet movement in Spain during the period of the Second Republic (1931-1936) and the Civil War (1936-1939), and investigates the community-based aspect of its schooling practices. To begin with, we examine a number of aspects of Spain’s Freinet movement which help to see it as a social movement as well as a pedagogical one. Then, we study a) the main strategies employed by teachers to facilitate the social building of democracy through the schooling system, and b) the most significant extensions of the school into the local community, which helped break down the physical and symbolic barriers separating schooling institutions from the framework of ordinary citizens’ daily existence.